Characterization of SSR genomic abundance and identification of SSR markers for population genetics in Chinese jujube (Ziziphus jujuba Mill.) - Peng-cheng Fu; Yan-Zhao Zhang; Hui-yuan Ya; Qing-bo Gao (PeerJ, 2016)
Chinese jujube (Ziziphus jujuba Mill. [Rhamnaceae]), native to China, is a major dried fruit crop in Asia. Although many simple sequence repeat (SSR) markers are available for phylogenetic analysis of jujube cultivars, few of these are validated on the level of jujube populations. In this study, we first examined the abundance of jujube SSRs with repeated unit lengths of 1–6 base pairs, and compared their distribution with those in Arabidopsis thaliana. We identified 280,596 SSRs in the assembled genome of jujube. The density of SSRs in jujube was 872.60 loci/Mb, which was much higher than in A. thaliana (221.78 loci/Mb). (A+ T)-rich repeats were dominant in the jujube genome. We then randomly selected 100 SSRs in the jujube genome with long repeats and used them to successfully design 70 primer pairs. After screening using a series of criteria, a set of 20 fluorescently labeled primer pairs was further selected and screened for polymorphisms among three jujube populations. The average number of alleles per locus was 12.8. Among the three populations, mean observed and expected heterozygosities ranged from 0.858 to 0.967 and 0.578 to 0.844, respectively. After testing in three populations, all SSRs loci were in Hardy-Weinberg equilibrium (HWE) in at least one population. Finally, removing high null allele frequency loci and linked loci, a set of 17 unlinked loci was in HWE. These markers will facilitate the study of jujube genetic structure and help elucidate the evolutionary history of this important fruit crop.